Pengaruh Motivasi Pemeliharaan Kesehatan Gigi dan Mulut terhadap Kehilangan Gigi pada Lansia (Studi di Lakukan di Posyandu Lansia Sekar Arum Kel. Kertajaya, Kec. Gubeng Surabaya) - Ayu Dwi Pradnyani; Bambang Hadi Sugito; Imam Sarwo Edi; Sri Hidayati (Borneo Nursing Journal (BNJ), 2026)
Tooth loss is a common oral health issue among the elderly that can affect chewing function, speech ability, nutritional status, and quality of life. Motivation regarding oral health maintenance is considered a potential factor in preventing tooth loss. This study aimed to analyze the influence of oral health maintenance motivation on tooth loss among the elderly at the Sekar Arum Elderly Integrated Health Post (Posyandu Lansia) in Kertajaya Village, Gubeng District, Surabaya City. A quantitative analytical design with a cross-sectional approach was employed. The study sample consisted of 54 respondents, determined using Slovin's formula and selected via simple random sampling. Oral health maintenance motivation was measured using a questionnaire, while tooth loss was assessed through intraoral examinations using an observation sheet. Data analysis was conducted using univariate and bivariate methods, specifically the Chi-square test with a significance level of 0.05. The results showed that the majority of respondents were aged 60–74 years (77.7%) and female (79.6%). Most respondents fell into the low category for oral health maintenance motivation (48.15%). Among respondents with a loss of ≥20 teeth, the majority were elderly individuals with low motivation (95.2%). The Chi-square test results indicated a significant influence of oral health maintenance motivation on tooth loss among the elderly (p=0.000). In conclusion, oral health maintenance motivation influences tooth loss in the elderly. Efforts to increase motivation through health education and oral health promotion are necessary to encourage oral health maintenance behaviors, thereby reducing the risk of tooth loss among the elderly.